2019
DOI: 10.1186/s13601-019-0270-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two multiplex arrays in the diagnostics of allergy

Abstract: The objective of this analysis was to compare the multiplex ImmunoCAP ISAC (Thermo Fisher Scientific, Sweden) and the multiplex Alex Allergy Explorer (Macro Array Diagnostics GmbH, Austria) platform on specific IgE to grass pollen (Phl p 1, Phl p 5), tree pollen (Bet v 1), house dust mites (Der p 1, Der p 2) and cat (Fel d 1) allergens in allergic patients. Our findings demonstrate a good correlation of presently used methods to detect serum sIgE. Multiplex testing of allergen-specific IgE can be the method of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 10 publications
3
20
0
4
Order By: Relevance
“…Correlations beyond 30 kUA/L between ALEX and ImmunoCAP require individual assessment of each allergen. For inhalant allergens, additional comparison studies have found significant correlations between ALEX and ISAC within three cohorts, 13,33,34 supporting the potential utility of these conversion methods for other allergens.…”
Section: Discussionmentioning
confidence: 84%
“…Correlations beyond 30 kUA/L between ALEX and ImmunoCAP require individual assessment of each allergen. For inhalant allergens, additional comparison studies have found significant correlations between ALEX and ISAC within three cohorts, 13,33,34 supporting the potential utility of these conversion methods for other allergens.…”
Section: Discussionmentioning
confidence: 84%
“…In brief, ALEX is a multiplex array containing 282 reagents (157 extractive allergens and 125 molecular components). The different allergens and components were coupled onto polystyrene nano-beads, and then, the allergen beads were deposited on a nitrocellulose membrane, as published elsewhere [26]. Total IgE levels were expressed in international units per unit volume (IU/mL), and sIgE levels were expressed in kU A /L.…”
Section: Methodsmentioning
confidence: 99%
“…The published data indicate that the results of the various in vitro tests are not comparable or interchangeable [23,[31][32][33]. Although there may be some degree of correlation between tests, the results are not interchangeable through conversion factors due to the lack of units referred to a common standard [23,[33][34][35][36][37].…”
Section: Considerations Before Switching To a Different In Vitro Assamentioning
confidence: 99%